Smart Practices Adopted By Indian Corporates To Increase Motivation Among Employees - Chauhan, Sweta (International Journal of Psychosocial Rehabilitation, 2019)
An employee is a company's lifeblood. Each employee contributes to the whole and works together to make the company a success. They are the bedrock of any administrative position. Workers cannot fulfill their function if they are not competent in their tasks. That's why it's important to provide enjoyable incentives for workers. An enthusiastic worker puts up extra effort. He or she is much more committed to their job now. This sort of action contributes more broadly to the company's goals. It's great that they're committed to staying put in their current position. The longer they stay with the company, the more of a treasure they become. Therefore, you should maintain parity in their compensation packages so that employees may operate without financial stress.